(untitled) (Advances in Knowledge Representation, 2021)
The act of classifying can be considered an indispensable process in the construction of Knowledge Organization Systems. In ontological systems, the attempt to classify the world divides opinions as to its viability and reliability. The generalization made from singular entities and its relation to knowledge is central to this issue. Using the distinction proposed by Bunge between substantial and conceptual universals, the relationship between ontological study, logic, and language is approached. The operation of “ontologization” of a language is described and the problematic use of logical language to deduce ontological categories is addressed. It concludes by clarifying the differences between the Platonic view associated with first-order logic and the so-called Aristotelian essentialism. The reflection presented suggests the need for the inclusion of the ontological approach as an interdisciplinary tool for a more comprehensive view of society.